Perancangan Aplikasi EMR (Electronic Medical Record) Dengan Menggunakan Kartu RFID Untuk Mencatat Data Rekam Medis Pasien Pada Puskesmas Sukajadi Bandung - Agung Rachmat Raharja; Ifani Hariyanti (Universitas Kebangsaan Republik Indonesia, 2023)
One of the supports for health services is required to be better, one of which is by making EMR (electronic medical record) applications using RFID cards as a substitute for patient medical record cards. In this case this RFID card can function as patient history data, when the patient taps the RFID card, then all the history data appears entirely. Problem Identification at this stage the author identifies the problems that occur and looks for solutions needed at the Sukajadi Community Health Center in Bandung which requires a medical record application system to assist in processing patient data, medical record data and drug data at the Sukajadi Community Health Center. This research resulted in the design of a Medical Record application at the Sukajadi Health Center, Bandung City using an RFID card. b. With the record application can help activities in managing data both patients and drug data and more efficient and safer so that doctors can add or view the patient's medical record history.